«КИТАБ ӘЛ-ИДРАК ЛИ-ЛИСАН ӘЛ-АТРАК» ҚОЛЖАЗБА ЕСКЕРТКІШІНІҢ ЛЕКСИКА-СЕМАНТИКАЛЫҚ ЕРЕКШЕЛІКТЕРІНЕ (СӨЗЖАСАМ) ШОЛУ - Есбосынов, Е. З. (Journal of Oriental Studies, 2018)
In this article, the word structure of middle century written manuscript Kitab al-İdrak li-Lisan al-Atrak was taken as a sentence structure, and the information about the grammatical properties was evaluated in terms of present-day Kazak linguistics. Ahmet Caferoğlu's book published in 1931 as the main source was published in the same name and the samples and sections were classified according to the grammatical and morphological analyzes mentioned.